Interventional low‐dose azithromycin attenuates cigarette smoke‐induced emphysema and lung inflammation in mice. Issue 13 (11th July 2020) - Macowan, Matthew G.; Liu, Hong; Keller, Marianne D.; Ween, Miranda; Hamon, Rhys; Tran, Hai B.; Hodge, Sandra
Abstract: Cigarette smoke (CS)‐induced emphysema is an important contributor to chronic obstructive pulmonary disease (COPD). We have shown the efficacy of azithromycin in reducing airway inflammation in COPD and in reducing exacerbations in severe asthma; however, the effects of long‐term azithromycin on emphysema development have not been shown. We employed live animal imaging to monitor emphysema‐like development and the effects of interventional azithromycin treatment in CS‐exposed mice. BALB/c mice (female, 10 weeks; n  = 10) were exposed to CS for 1 hr twice daily, 5 days/week, and for 12 weeks (CS). Half were cotreated with low‐dose azithromycin during weeks 7–12 (CS + Azi; 0.2 mg kg −1  day −1 ). Microcomputed tomography (CT) and magnetic resonance imaging (MRI) scans were acquired longitudinally. Histological examinations were performed post mortem (mean linear intercept (Lm) and leukocyte infiltration). CS increased median Lm (CS: 42.45 µm versus control: 34.7 µm; p  = .0317), this was recovered in CS + Azi mice (33.03 µm). Average CT values were reduced in CS mice (CS: −399.5 Hounsfield units (HU) versus control: −384.9 HU; p  = .0286) but not in CS + Azi mice (−377.3 HU). CT values negatively correlated with Lm ( r  = −.7972; p  = .0029) and T2 ‐weighted MRI ( r  = −.6434; p  = .0278). MRI also showed significant CS‐induced inflammatory changes that were attenuated by azithromycin in the lungs, and positively correlated with Lm ( r  = .7622; p  = .0055) and inflammatory foci counts ( r  = .6503; p  = .0257). Monitoring of emphysema development is possible via micro‐CT and MRI. Interventional azithromycin treatment in CS‐exposed mice attenuated the development of pulmonary emphysema‐like changes. Abstract :